Sport Injuries Aligned to Peak Height Velocity in Talented Pubertal Soccer Players - van der Sluis, A.; Elferink-Gemser, M. T.; Coelho-e-Silva, M. J.; Nijboer, J. A.; Brink, M. S.; Visscher, C. (International Journal of Sports Medicine, 2014)
In young athletes, demands of sports are superimposed on normal growth and maturation. It has been suggested that this causes a temporarily increased vulnerability for injuries. We followed 26 talented soccer players (mean age 11.9±0.84 years) longitudinally for 3 years around their adolescent growth spurt, called Peak Height Velocity, to identify differences in number of traumatic and overuse injuries and days missed due to injuries. Peak Height Velocity was calculated according to the Maturity Offset Protocol. The number of injuries was calculated for each player per year. A repeated measurement analysis showed that athletes had significantly more traumatic injuries in the year of Peak Height Velocity (1.41) than in the year before Peak Height Velocity (0.81). A moderate effect size of 0.42 was found for the difference in number of overuse injuries per player per year before (0.81) and after Peak Height Velocity (1.41), respectively. Finally, a moderate effect size of 0.55 was found for difference between days missed due to injuries before (7.27 days per player per year) and during Peak Height Velocity (15.69 days per player per year). Adolescent growth spurt seems to result in increased vulnerability for traumatic injuries. Afterwards athletes seem to be susceptible to overuse injuries.
Keywords: growth spurt; development; trauma; maturity; longitudinal study; sport; adolescent